Health Education Characters in Early Childhood Based on Cultural Values - Siti Nurlatifah (SEA-CECCEP, 2021)
This study seeks to produce a character education model for healthy living in early childhood based on character values. In producing this model, the researcher uses four stages that must be taken, namely define, design, develop and desiminate. At the define stage, the researcher made preliminary observations by collecting how the description of healthy life character education activities carried out by schools has been done by collaborating with cultural values, both classroom, school and environment or community culture. The figures for each variable are calculated based on the observation questionnaire compiled by the researcher. Based on preliminary observations based on interviews of healthy living character education comprehensively, it has been established by schools, both teachers and students, but there is no evaluation whether the healthy living character education is developed based on cultural values Furthermore, the researcher will explore in depth how the knowledge, implementation and feelings of students towards the character of a healthy life. Cultural values ​​that can be implemented properly based on the results of observations show that the three cultural values ​​influence each other on the formation of healthy living characters for early childhood.